Attosecond Photoelectron Spectroscopy of Metal Surfaces - Zhang, C.-H.; Thumm, U. (My University, 2009)
Recent attosecond-streaking spectroscopy experiments [A. L. Cavalieri et al., Nature (London) 449, 1029 (2007)] using copropagating extreme ultraviolet (XUV) and infrared (IR) pulses of variable relative delay have measured a delay of approximately 100 attoseconds between photoelectrons emitted by a single XUV photon from localized core states and delocalized conduction-band states of a tungsten surface. We analyze the underlying XUV-photoemission–IR-streaking mechanism by combining a perturbative description of the XUV-photoemission process and the subsequent nonperturbative IR streaking of the photoelectrons. Our calculated time-resolved photoelectron spectra agree with the experiments of Cavalieri et al. and demonstrate that the observed temporal shift is caused by the interference of core-level photoelectrons that originate in different layers of the solid.